Struktur Komunitas Dan Pola Sebaran Jenis Lamun Di Pantai Batu Jimbar Sanur Bali - Constantein Petta; I Ketut Sudiarta; I Gede Sudiarta (GEMA AGRO, 2021)
Spread over about 1 km of coastal line area, Batu Jimbar Beach displays stretch of seagrass beds along its coastline and for approximately 0,4 km towards the sea. This beach is a well-known site for both tourism and fishery activities, including fishing and boat landing. Those both activities are certainly bring out impacts on the stability of the seagrass ecosystem. In connection with that matter, this study aims to determine the community structure and distribution pattern of seagrass species at Batu Jimbar Beach. The research was taken place in February - June 2021, and was carried out by using descriptive methodology. Observation for research was conducted at three research stations which were divided into three sub-stations. It resulted that the seagrass community consisted of 9 species, including: Enhalus acroides, Halophila ovalis, Thalassia hemprichii, Cymodocea rotundata, Cymodocea serrulata, Halodule pinifolia, Halodule uninervis, Syringodium isoetifolium and Thalassodendron ciliatum. The most coverage found was Thalassia hemprichii (60.19%) and the least coverage in species composition was Cymodocea cerulata and Thalassodendron ciliatum (0.31%). According to the research stations’ data, the density of the observed seagreass ranged from 284 – 327 ind/m2 with a cover percentage between 51.1 – 55.2%. The diversity index according to research stations was also ranged from 1.06 to 1.16, while the uniformity index ranged from 0.59 to 0.66, and the dominance index ranged from 0.43 to 0.49. Also, the species similarity index between research stations was 100%. The research was also discoverd that the distribution pattern of seagrass species is clustered.